Optimalisasi Peran Auditor Internal Melalui Penerapan Good Corporate Governance (GCG) untuk Meningkatkan Kinerja Keuangan pada Instansi Perwakilan BKKBN DIY - Vina Sopiani (Program Studi Manajemen, 2020)
This study aims to determine the implementation of Good Corporate Governance (GCG) on financial performance at BKKBN DIY Representatives, the role of internal auditors in optimizing Good Corporate Governance (GCG) at BKKBN DIY Representatives, and obstacles in optimizing Good Corporate Governance (GCG) at BKKBN DIY Representatives.Through descriptive qualitative research methods, by interviewing 5 employees who are a team of auditors, latbang, and treasurer expenditures and make observations. From the results of the research on the implementation of GCG at the BKKBN DIY Representative Office, it is optimal because it can minimize the occurrence of irregularities and make financial management easier, the role of auditors on financial performance is optimal because auditors always carry out their roles properly, namely as quality assurance and consultants, although there are still obstacles to optimizing. GCG but it can still be resolved.